Phytochemical, Pharmacognostic and Elemental Analysis of Cayratia gracilis (Guill. & Perr.) Suesseng - Egharevba O. Henry, Ibrahim A. Jemilat, Mustapha B. Kudirat, Ezenwa O. Uche, Okhale E. Samuel (Journal of Applied Pharmaceutical Science, 2015)
The plant Cayratia gracilis (Guill. & Perr.) Sues., family Vitaceae, is renowned for its numerous medicinal application in folks medicine especially for its analgesic properties. Phytochemical, physicochemical, microscopic and elemental analyses were carried out on the plant to establish basic monograph information for authentication of the plant samples. The moisture content was 12.7%, water extractive value was 19%, and alcohol extractive value was 3.9% in the leaves and the moisture content of 8.8%, water extractive value of 14.8% and alcohol extractive value of 1.3% in the stem. Phytochemical screening revealed the presence of 8 secondary metabolites for the leaves and 6 for the stem. The thin-layer chromatographic (TLC) profile of the stem revealed 4, 3, and 2 spots for the hexane, ethyl acetate and methanol extracts respectively, while the leave revealed 5, 2 and 4 clear spots for hexane, ethyl acetate and methanol extracts respectively. Atomic Absorption Spectroscopy (AAS) of the plant shows the presence Zn, Cu, Mn, Mg, Fe, Na, and absence of metals like Pb and Cr. The study reveals microscopic characters that are useful as diagnostic parameters for Cayratia gracilis. Information obtained from this study is important in establishing diagnostic indices for identification, standardization, and also in monograph development of the plant which has ethno-medicinal uses.
Keywords: Microscopy, Physicochemical, Chromatograph, AAS, Elemental, Standardization.